Avaliação das comunidades de bacteria, archaea e vírus entéricos do esgoto sanitário do aeroporto e da rodoviária de Belo Horizonte - André Felipe Leal Bernardes (2017)
The one health one world concept is related to an interdisciplinary knowledge that targets the control of zoonosis and infectious diseases dissemination. In this sense, environmental health gives crucial information and plays an important role in preventive health. The increase of people circulation between different geographical areas increases the concern regarding the fact that microorganisms harboured by travelers may be introduced in these areas. Therefore, when using public toilets such microorganisms may be eliminated and after this they may circulate through sanitary sewage. Airports and bus stations require special attention. Metagenomics and qPCR are considered as adequate tools to be used in studies that aim to evaluate microbial diversity in a wide range of environments. This investigation addressed the microbial diversity of sanitary sewer of Carlos Drummond de Andrade Airport and Governador Israel Pinheiro Bus Station, Belo Horizonte, places where a lot of people from different regions circulate. In 2016 two samples have been collected from these places one in an ordinary day and another one in a day with increased circulation of people. The collected samples were centrifuged and submitted to DNA and RNA extraction. After that we investigated enteric viruses (enterovirus, adenovirus, rotavirus e hepatitis A and E viruses), Bacteria, and Archaea. All enteric viruses have been detected in at least one sample obtained from each studied place. The relative abundance of Bacteria was higher than that of Archaea. Firmicutes presented the higher relative abundance, mainly when more people circulated in the airport and bus station. Aeromonas and Arcobacter, considered as potential pathogens, have also been detected in all studied samples. Environmental monitoring associated to the concept of One Health helps preventing infectious diseases constituting a relevant tool and may contribute to the development of public politics to protect, promote, and restore collective health.